2019
DOI: 10.18415/ijmmu.v6i1.511
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Posyandu as Primary Health Care Services in Implementing Early Detection and Intervention for Autistic Children in Indonesia

Abstract: Autism is one of the most complex developmental disorder in children. In the developing country, Autism is a new paradigm, it causes various problems in autism service especially in early detection. It is caused by several factors that interconnected, such as the low understanding of society about autism, the low public awareness about the importance of early detection of autistic children, and the less prioritized attention from the government. Expanding the accessibility of autism services through primary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Working mothers tend to take their babies to a doctor's clinic or to midwives' independent practice to be immunized because they have to work in the morning. [19][20][21] Other studies have shown that employed mothers tend to have higher levels of stress and lower levels of overall well-being than mothers who are not employed. 22,23 This suggests that employment status can have both positive and negative effects on mothers' ability to access healthcare for their babies.…”
Section: Discussionmentioning
confidence: 99%
“…Working mothers tend to take their babies to a doctor's clinic or to midwives' independent practice to be immunized because they have to work in the morning. [19][20][21] Other studies have shown that employed mothers tend to have higher levels of stress and lower levels of overall well-being than mothers who are not employed. 22,23 This suggests that employment status can have both positive and negative effects on mothers' ability to access healthcare for their babies.…”
Section: Discussionmentioning
confidence: 99%
“…22 Pendapat diatas sejalan dengan penelitian lainnya bahwa posyandu memiliki peran untuk memberikan informasi kesehatan bagi masyarakat dan sebagai pendorong masyarakat dalam menerapkan perilaku hidup bersih dan sehat, sehingga kader posyandu sebagai agent of change perlu juga untuk dibekali pengetahuan yang mumpuni dalam mendeteksi dini dan intervensi dini keadaan kesehatan balita termasuk anak berkebutuhan khusus seperti autis. 23 Program kesehatan ibu dan anak merupakan program pengembangan kesehatan ibu/perempuan. Perempuan adalah tulang ©2021, JEKK, All Right Reserved punggung sebuah negara terlebih lagi seorang ibu, sehingga apabila tulang punggung negara itu rapuh maka tidak akan mampu menopang keberlangsungan sebuah negara.…”
Section: Metodeunclassified
“…Efforts in human development must be prioritized from the start, from pregnant mothers, infants who are breastfed and immunized, to the elderly [7]. In light of the disparity in nutritional status among toddlers in Indonesia, the government is trying to improve this by providing healthcare services through integrated service centers, also known as Posyandu [8]. Posyandu is a form of active community participation in improving the health of the local community.…”
Section: Introductionmentioning
confidence: 99%